Perancangan Sistem Informasi Dokumen P44(Hasil Putusan) Berbasis Web Studi Kasus Kejaksaan Negeri Deli Serdang - Ryo Vikri Alif; Muhammad Reza Alhafiz; M. Fakhriza (CV. ITTC INDONESIA, 2024)
The development of information technology has become a necessity in optimizing the management of legal documents, especially P44 documents (judgment results). The success of a legal institution depends greatly on its ability to manage and access legal documents, including the results of P44 decisions, quickly and accurately. The process of managing P44 documents at the Deli Serdang District Prosecutor's Office still faces various obstacles. Therefore, there is a need for solutions that can improve the quality of managing P44 documents. Based on these problems, a web-based p44 (decision result) document information system was created. This research uses a Research and Development (RnD) approach with the aim of designing and developing electronic mail. With this system, it is hoped that it can increase accessibility, efficiency and security in managing P44 documents and support the operational performance of the Deli Serdang District Prosecutor's Office as a whole.